Manifestation of multiphonon structure and orbitons in the tunnel spectra of manganites - Svistunov, V.M.; Leonova, V.N.; Belogolovskii, M.A.; Revenko, Yu.F. (Functional Materials, 2009)
The study results of the tunnel conductance of heterostructures formed by a silver tip and a doped Ag/La₀.₅₇Ca₀.₄₃MnO₃ manganite in the voltage region above manganite phonon and magnon frequencies are presented. Three maxima have been observed at energies corresponding to the peaks in the Raman spectra of LaMnO₃. It is supposed that the maxima are due to the interaction of tunneling electrons with excitations in the orbital subsystem of a degraded region nearby the metal-manganite interface.